Глиняні форми для виготовлення скляних посудин (за даними розкопок середньовічного виробничого комплексу Київського Подолу) - Сергеєва, М.С.; Журухіна, О.Ю. (Археологія і давня історія України, 2018)
У статті йдеться про знахідку чотирьох глиняних форм для виготовлення тонкостінного скляного посуду. Форми виявлено під час розкопок комплексу ХІІ —ХІІІ ст. в одній з частин виробничого кварталу Київського Подолу. A unique find of four clay molds for making glass
vessels was found during archaeological researches of
the site on the Naberezhno-Khreshchatitska str., 21
(Kyiv Podil) in 2007. The excavations both on the street
itself and on the bordering areas revealed the existence
here of a large handicraft quarter with economic and
production objects dated to the 11th and 12th centuries.
Location of the studied site near the waterway (Dnieper
River) was convenient for placing here fire-hazardous
productions, such as glass-making workshops.
On the site, remains of the construction of the furnace
in the form of large pieces of vitrified clay and
fragments of plinth form bricks were fixed. Numerous
pieces of glass were found, as well as fragments of glassware, mainly those of bracelets and vessels. Among another
finds there were such glass ornaments as beads and rings, and one inset for the ring. Among the ceramic
material from the investigated complex, there were four clay molds for forming glass vessels. The
molds were of bowl-like form and had a ribbed inner surface, made by hand. It is worthy to note that among
the products there were two fragments of glass bottoms with ribbed outer surfaces, which could be made
in such molds. Vessels with ribbed walls appear on the territory of Ancient Rus’ from the second half of the
12th century. Chemical analyzes of glass mass taken from the complex showed that samples could be identified
as lead-potassium Ancient Rus’ glass. Glassware, certain materials (molds for glass vessels,
crucibles, pieces of lead), allow to connect the excavated complex with glass-making production.